Nicholas Biddle papers - Biddle, Nicholas, 1786-1844.
Correspondence, letterbooks, account books, and writings pertaining primarily to Biddle's career as president of the Bank of the United States (1822-1839). Subjects include the attitude of the U.S. president, Congress, and the public toward the bank; Biddle's student life at Princeton University; his position as secretary of the American legation in Paris; his editorship of and contributions to Port Folio magazine; his work as a member of the Pennsylvania legislature; his business and social affairs; and farming. Includes Biddle (Bedell) family papers concerning Charles, Clement, Edward, James, Nicholas, Thomas, and William S. Biddle.
Correspondents include Horace Binney, John C. Calhoun, Thomas Cooper, Alexander James Dallas, Asbury Dickins, James Hamilton, Charles Jared Ingersoll, Abbott Lawrence, Charles J. Lewis, Francis Lieber, Edward Livingston, George McDuffie, John McLean, John Tyler, John G. Watmough, and Daniel Webster.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Banker, diplomat, editor, lawyer, and legislator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Biddle, Charles, -- 1745-1821.; Biddle, Clement, -- 1740-1814.; Biddle, Edward, -- 1738-1779.; Biddle, James, -- 1783-1848.; Biddle, Thomas, -- 1776-1857.; Biddle, William S; Binney, Horace, -- 1780-1875 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Cooper, Thomas, -- 1759-1839 -- Correspondence; Dallas, Alexander James, -- 1759-1817 -- Correspondence; Dickins, Asbury, -- 1780-1861 -- Correspondence; Hamilton, James, -- 1786-1857 -- Correspondence; Ingersoll, Charles Jared, -- 1782-1862 -- Correspondence; Lawrence, Abbott, -- 1792-1855 -- Correspondence; Lewis, Charles J. -- Correspondence; Lieber, Francis, -- 1800-1872 -- Correspondence; Livingston, Edward, -- 1764-1836 -- Correspondence; McDuffie, George, -- 1790-1851 -- Correspondence; McLean, John, -- 1785-1861 -- Correspondence; Tyler, John, -- 1790-1862 -- Correspondence; Watmough, John G. -- 1793-1861 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Bedell family; Pennsylvania. -- General Assembly; United States. -- Legation (France); Bank of the United States (1816-1836); Princeton University; Port folio (Philadelphia, Pa. : 1801); Agriculture -- Pennsylvania; Diplomatic and consular service, American -- France; Universities and colleges -- New Jersey; Pennsylvania -- Commerce; Pennsylvania -- Politics and government -- 1775-1865.; Pennsylvania -- Social life and customs; United States -- Economic policy; Bankers; Diplomats; Editors; Lawyers; Legislators -- Pennsylvania